Evaluation of Electrocardiographic Changes in Girls Receiving Gonadotropin-Releasing Hormone Analogs for Precocious Puberty - Eren Er; Aysun Ata; Ali Orgun (Galenos Yayinevi, 2023)
Aim:Gonadotropin-releasing hormone analogs (GnRHa) are standard medical treatments for precocious puberty. Studies on their side effects in adults have shown that these drugs can cause changes in electrocardiography (ECG), along with some cardiovascular effects; however, the number of studies on children is limited. This study investigated the effects of these drugs on ECG parameters in children diagnosed with central precocious puberty (CPP).Materials and Methods:This prospective study included 44 girls who were initiated GnRHa treatment and diagnosed with CPP. ECG was performed before treatment and repeated after 6 months of treatment.Results:The mean age of the children was 9.13±1.55 years. Leuprolide acetate (3.75 mg IM) was administered to all of the patients following the standard protocol. A comparison of the pre-treatment and 6-month ECG parameters revealed a prolonged QT interval after treatment, with a statistically significant difference (p<0.001). There were no significant differences in the pre- and post-treatment values of PR, QRS, QT interval, QTc interval, QT dispersion, or QTc dispersion (p>0.05).Conclusion:Despite a significant increase in QT interval on ECG with GnRHa compared to pre-treatment ECGs, this increase was attributed to a variability in heart rate. Even if regular ECG monitoring is considered after initiation of GnRHa treatment, they are believed to be safe drugs in children.